Cold-tolerant phosphate-solubilizing Pseudomonas strains promote wheat growth and yield by improving soil phosphorous (P) nutrition status - Dasila, Hemant; Sah, V. K.; Jaggi, Vandana; Kumar, Arun; Tewari, Lakshmi; Taj, Gohar; Chaturvedi, Sumit; Perveen, Kahkashan; Bukhari, Najat A.; Siang, Tan Ching; Sahgal, Manvika (Frontiers in Microbiology, 2023)
It is well-known that phosphate-solubilizing bacteria (PSB) promote crop growth and yield. The Information regarding characterization of PSB isolated from agroforestry systems and their impact on wheat crops under field conditions is rarely known. In the present study, we aim to develop psychrotroph-based P biofertilizers, and for that 4 PSB strains (Pseudomonas sp. L3, Pseudomonas sp. P2, Streptomyces sp. T3, and Streptococcus sp. T4) previously isolated from 3 different agroforestry zones and already screened for wheat growth under pot trial conditions were evaluated on wheat crop under field conditions. Two field experiments were employed; set 1 includes PSB + recommended dose of fertilizers (RDF); set 2 includes PSB-RDF. In both field experiments, the response of the PSB-treated wheat crop was significantly higher compared to the uninoculated control. In field set 1, an increase of 22% in grain yield (GY), 16% in biological yield (BY), and 10% in grain per spike (GPS) was observed in consortia (CNS, L3+P2) treatment followed by L3 and P2 treatments. Inoculation of PSB mitigates soil P deficiency as it positively influences soil alkaline phosphatase (AP) and soil acid phosphatase (AcP) activity which positively correlated with grain NPK %. The highest grain NPK % was reported in CNS-treated wheat with RDF (N-0.26%, P-0.18%, and K-1.66%) and without RDF (N-0.27, P- 0.26 and K-1.46%) respectively. All parameters, including soil enzyme activities, plant agronomic data, and yield data were analyzed by Principal component analysis (PCA) resulting in the selection of 2 PSB strains. The conditions for optimal P solubilization, in L3 (temperature-18.46, pH-5.2, and glucose concentration-0.8%) and P2 (temperature-17 oC, pH-5.0, and glucose concentration-0.89%) were obtained through Response surface methodology (RSM) modeling. The P solubilizing potential of selected strains at less than 20° C makes them a suitable candidate for the development of psychrotroph-based P biofertilizers. Low-temperature P solubilization of the PSB strains from agroforestry systems makes them potential biofertilizers for winter crops.